Clavicle Morphometry for Sexual Dimorphism and Bilateral Asymmetry: Radiographic Assessment - KC, Sudikshya; Shrestha, Subina; Acharya, Sumnima; Bhandari, Keshav Raj (Journal of Nepal Health Research Council, 2020)
Background: The clavicle, modified long bone, presents morphological and bilateral variations. This may be due to genetic factors, hormones, or environmental and occupational influences. Anthropometric studies in clavicle of Nepalese population using radiograph has not been reported to best of our knowledge. This study, aimed to determine the sexual dimorphism and bilateral asymmetry of clavicle in Nepalese Population using Postero-Anterior Chest X Ray. Methods: Chest x-rays with normal and clearly visible both clavicles of 1260 Nepalese adults (591 male, 669 female), aged above 20 years were utilized. Inbuilt software “Computed Radiography Fuji Computer System 7” was used for measurements (in centimeter) of sternal head length, acromial end length, mid shaft diameter and length of clavicle. Demarcating point and identification point were calculated. Patients having history of clavicles fractures in the past were excluded. Results: All the parameters in male is greater than female which is significant except Length/Mid Shaft Diameter. Similarly, all the parameters of right clavicle is significantly greater than left clavicle in both sexes except Sternal Head Length and Mid Shaft Diameter. Demarcating point calculated from length of the clavicle (right >16.17, left >16.10 for male and right <11.20, left <10.65 for female) and Mid Shaft Diameter (right >1.33, left >1.38 for male and right <0.66 and left <0.67 for female) are important parameters to determine sex. Conclusions:The clavicle shows significant sexual dimorphism and bilateral asymmetry in Nepalese population. The result of this study is helpful to anthropologist and forensic medicine. Keywords: Anthropometry; clavicle; demarcating point; postero-Anterior chest x-rays; sexual dimorphism